PENANAMAN KARAKTER RELIGIUS DAN TOLERANSI MELALUI PEMBELAJARAN FIQIH PADA SISWA KELAS IX DI MADRASAH TSANAWIYAH TARBIYATUL MUBTADIIN WILALUNG DEMAK - Purwato Purwanto; Mukh Nursikin (Universitas Islam Madura, 2023)
Education there are still problems in adolescents that do not reflect religious attitudes and tolerance due to a lack of understanding of Islamic law. This study aims to determine the design, implementation and evaluation of cultivating religious character and tolerance through learning fiqh. This research method uses a descriptive qualitative approach with a phenomenological type involving informants from Madrasah Heads, Fiqh Teachers, and Grade IX students. The collection of data used is observation, interviews, and document study. The results of the study found that the cultivation of religious character and tolerance through learning fiqh is a learning design that includes steps in cultivating religious character and tolerance. Implementation of interactive classroom learning, carrying out habituation activities outside the classroom to instill religious character, in the form of: dhuha prayers and congregational midday prayers, extracurricular muhadharah, while to instill the character of tolerance through discussion activities in class learning, and extracurricular bahtsul masail. Evaluation is carried out using an attitude scale, which is measured by a scoring system, including: always, often, sometimes and never, which is carried out in the learning process in class, habituation activities, and extracurricular activities. The implication of this research is that education managers can easily understand that every lesson including fiqh subjects can be accustomed to positive and religious characters.